1984
DOI: 10.1017/s0022172400064718
|View full text |Cite
|
Sign up to set email alerts
|

A study of Coxsackie B virus infections, 1972–1983

Abstract: SUMMARYThe results of a twelve-year study of Coxsackie B virus (CBV) infections in patients with a variety of acute and chronic illnesses are reported. CBVs were isolated from only 123 patients most of whom were children with respiratory illness. Virus diagnosis in adults was based mainly on the detection of significant rising or static high neutralizing antibody titres. Between 1972 and 1979 most investigations centred on patients with suspected viral heart disease, 12 % of whom were found to have diagnostica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Many viruses, notably the enteroviruses, have been implicated in the aetiology of CFS [23]. Neutralizing antibody to Coxsackie B virus (CBV) is commonly found in the blood [24][25][26][27]. Coxsackie virus-specific RNA has been reported in skeletal muscle biopsies [28,29].…”
Section: Virusesmentioning
confidence: 99%
“…Many viruses, notably the enteroviruses, have been implicated in the aetiology of CFS [23]. Neutralizing antibody to Coxsackie B virus (CBV) is commonly found in the blood [24][25][26][27]. Coxsackie virus-specific RNA has been reported in skeletal muscle biopsies [28,29].…”
Section: Virusesmentioning
confidence: 99%
“…It is possible that both a particular genetic make-up of the host and the appropriate strain are necessary for diabetogenesis, as proposed by Roivainen et al [7]. In addition, studies in the past have revealed that, at least for some individuals, infection with a different Coxsackievirus B serotype can increase the levels of antibody against a previously infecting serotype (heterotypic response) [8]. The lack of uniformity of presence of antibodies against all serotypes at old ages argues against heterotypic antibody responses being common.…”
Section: Discussionmentioning
confidence: 99%
“…Coxsackieviruses have the potential to cause a wide variety of symptoms in a normally healthy host. These include high fever, vomiting, abdominal pain, headache, rash, jaundice, and diarrhea, and serious health outcomes such as aseptic meningitis (Bell & McCartney, 1984), myocarditis (Bowles et al, 1986; Reyes & Lerner, 1985; Bell & McCartney, 1984; Kaplan et al, 1983; Artenstein et al, 1965), respiratory illness (Bloom et al, 1962), encephalitis (Bowles et al, 1986; Reyes & Lerner, 1985; Moore et al, 1984; Kaplan et al, 1983; Artenstein et al, 1965; Bloom et al, 1962), and insulin‐dependent diabetes mellitus (IDDM) (Frisk et al, 1992; Sumbureru, 1991; Yoon, 1990; Barrett‐Connor, 1985; Bell & McCartney, 1984). Because of this range of symptoms and outcomes, outbreaks as well as the importance of coxsackievirus infections may go unrecognized.…”
Section: Coxsackievirus Backgroundmentioning
confidence: 99%